Estructuración de un mecanismo que viabilice la aplicación de balanced scorecard en la empresa “prime injection” ubicado en la ciudad de Guayaquil - Logroño Cordero, Jorge David (2015)
In the development of this project has been considered as a subject of research for "PRIME INJECTION", this company has a laboratory activity and spare parts for diesel injection systems, gasoline turbos since 2011. The fast forward technology now allows companies a broader and shorter in terms of development time, which is why providers that are dedicated to providing the supplies, materials and equipment should be in line with technological developments, this implies that increases demand for these, thus raising competition, which is why "PRIME INJECTION" offers reliable and agile suppliers.